TIMING SHAFT SEBAGAI PENGGERAK CAM SHAFT DALAM MOTOR SISTEM 4 TAK - Hidayat, Wahyu (RESULTAN : Jurnal Kajian Teknologi, 2010)
The drive cam shaft is important element from mechanic valve drive on four stroke engine, because useful for connecting rotation from crank shaft to cam shaft. Mechanic valve works to  arrange the performance of valves in agreement with stroke engine. The connecting drive valve on modern motor there are two types; there are timing belt. The new inovation can use timing shaft which bevel gears on each of shaft, crank shaft and cam shaft. to use timing shaft, the sistem of mechanic valve have to work effectively.